2021
DOI: 10.3389/fmats.2021.783239
|View full text |Cite
|
Sign up to set email alerts
|

A Theoretical Perspective on Strategies for Modeling High Performance Nonlinear Optical Materials

Abstract: Nonlinear optical (NLO) materials have spanned a large area of science and technology owning to their potential applications in optoelectronics. The invention of the first Ruby laser has sparked a fresh interest in the area of nonlinear optics. The computational designing and experimental synthesis of organic and inorganic NLO materials with higher order nonlinearities come into vogue in the field of materials science. To date, several strategies including metal ligand framework, push pull mechanism, diradical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 245 publications
(235 reference statements)
0
22
0
Order By: Relevance
“…Before concluding, we compare our obtained NLO properties (second hyperpolarizability) to those of the most promising materials for NLO applications. According to Bano et al, 68 there are some strategies for the enhancement of the NLO response, including electron donor to acceptor push−pull mechanisms, 69 designing octupolar molecules, introducing diffuse excess electrons, 70 using multidecker sandwich clusters, applying bond length alteration theory, 71 designing metal organic frameworks (MOFs), etc. Among all considered systems within this review, since each strategy comprises a group of complexes, our model of Bi 60 shows an exceptionally large NLO response of 13.5 × 10 5 au (22 500 au/ atom).…”
Section: Exohedral Decorated Fullerenesmentioning
confidence: 99%
“…Before concluding, we compare our obtained NLO properties (second hyperpolarizability) to those of the most promising materials for NLO applications. According to Bano et al, 68 there are some strategies for the enhancement of the NLO response, including electron donor to acceptor push−pull mechanisms, 69 designing octupolar molecules, introducing diffuse excess electrons, 70 using multidecker sandwich clusters, applying bond length alteration theory, 71 designing metal organic frameworks (MOFs), etc. Among all considered systems within this review, since each strategy comprises a group of complexes, our model of Bi 60 shows an exceptionally large NLO response of 13.5 × 10 5 au (22 500 au/ atom).…”
Section: Exohedral Decorated Fullerenesmentioning
confidence: 99%
“…48 Other inorganic nanocages doped with superalkalis show enhanced NLO responses as well. 49,50 O 12 shows the highest NLO response of 3.94 × 10 5 au. 52 Some superalkalis show an ionization potential of 3.0 eV, which is much smaller than that of cesium metal (3.89 eV).…”
Section: Introductionmentioning
confidence: 96%
“…48 Other inorganic nanocages doped with superalkalis show enhanced NLO responses as well. 49,50 Ullah et al designed Li 2 F, Li 3 O, and Li 4 N superalkali doped B 12 P 12 nanocages for this purpose, with Li 2 F@B 12 P 12 having the highest NLO response of 3.48 × 10 5 au. 51 Theoretical investigations into the Li 3 O, Na 3 O, and K 3 O superalkali doping of Zn 12 O 12 nanocage revealed that K 3 O@Zn 12 O 12 shows the highest NLO response of 3.94 × 10 5 au.…”
Section: Introductionmentioning
confidence: 99%
“…According to the literature ( vide supra ), numerous strategies have been proposed to design and synthesize highly efficient nonlinear optical materials such as doping, the push–pull mechanism, extensive π-electronic conjugation, and intramolecular charge transfer . Conducting polymers have extensively been studied theoretically by us and others regarding doping, sensors, and composite formation with other nanomaterials and for resolving structural ambiguities. It has been observed that polaronic states of conducting polymers have absorption spectra in red to near-infrared (NIR) regions.…”
Section: Introductionmentioning
confidence: 99%